“Laut adalah Ibu”: Bagaimana Peneliti Perempuan Usia Muda Memaknai Relasi Gender dalam Memproduksi Ilmu Pengetahuan: HOW YOUNG WOMEN SCIENTISTS DEMONSTRATE THE GENDER RELATIONS IN KNOWLEDGEPRODUCING - Ocktaviana, Sentiela; Ratri, Annisa Meutia (Jurnal Masyarakat dan Budaya, 2023)
The lack of representation of women in the fields of Science, Technology, Engineering and Mathematics (STEM) has become concern of many countries for decades. Gender inclusivity in development must also include gender equality in the science production. Considering the marine resources in Indonesia, the involvement of young female scientists in the development of marine science is necessity. By using an intersectionality approach, this study aims to reveal the experiences of young women as marine researchers and reveal their strategies, not only in maintaining their careers, but also in developing and producing knowledge. The concept of intersectionality is used to identify every element that influences and shapes gender identity. Women’s identity cannot be separated from the relationships that occur in both private and public spaces. Therefore, by using in-depth interview techniques, this research emphasizes women’s experiences about gender identity and gender relations. Through these women’s personal experiences, it is revealed that the identities of women researchers are formed from many factors, both internal and external, influencing how they make decisions, behave, strategize, and interact. However, those young women are still faced with structural and cultural barriers such as gender expectations, both in public and private spaces. The process of developing and producing knowledge cannot be separated from their gender identity as well as gender relations, including the relation between female researchers with their research object. The attachment of female researchers to their research objects and the sea that relate to their gender identity appears in the form metaphor of non-human objects. This study also reveals the concerns and hopes of young female researchers to be a consideration in formulating policies related to gender inclusivity in the STEM, especially in the marine science which can accommodate the uniqueness of gender identity.